DDIS-27. TARGETING ATP DOCKING AND P35/P25 BINDING OF CDK5 IN GLIOMA STEM CELLS USING SYNTHETIC INHIBITORS. (11th November 2019) - Mukherjee, Subhas; Schiltz, Gary; Clutter, Matt; Mishra, Rama; Olson, Cheryl; Dunder, Bilge; Sharma, Nitya; Markwell, Steven; Brat, Daniel
Abstract: The survival advantage of glioma stem cells (GSCs) represents a critical mechanism for growth, therapy resistance and recurrence in glioblastoma. So far, targeting GSCs has not been highly specific, since these cells co-opt the normal developmental signaling pathways. We have demonstrated that the activated CDK5-CREB1 signaling axis regulates GSC self-renewal and also promotes radiation-resistance. Thus targeting CDK5 signaling is highly rational, yet there are challenges. Most of the available CDK5 inhibitors also target other CDKs non-specifically. In collaboration with The Center for Molecular Evolution and Drug Discovery, we are developing novel CDK5 inhibitors that are highly potent and specific. METHODOLOGY: The CKD5-p25 crystal structure (pdb code 1UNL) was used to conduct a virtual high throughput screen (vHTS). A library of 10 million commercially available compounds which had been filtered to ensure they possessed good drug-like properties was screened against the crystal structure. The top 33 compounds based on their predicted target binding, synthetic feasibility and availability were tested in an in vitro kinase assay to measure CDK5 inhibition. RESULTS: Of the 33 potential hit, 11 compounds showed a CDK5 inhibition of < 50 µM. These 11 hits represent 4 distinct chemical scaffolds. Two of them have IC50 < 1 µM, with one compound having an IC50 < 0.4 µM. The vHTS and subsequent in vitro testing have therefore confirmed the identification of several new series of potent CDK5 hit compounds. We are now characterizing the kinase selectivity of our different hit series and evaluating their activity in cell-based assays. This will help focus efforts on the most promising 1–2 scaffolds for further medicinal chemistry optimization to improve the compounds' potency, selectivity and brain penetration. Ultimately, our optimized compounds will be tested in GBM models to demonstrate their effectiveness in inhibiting CDK5 as a new approach for treating GBM.